2015
DOI: 10.1038/bjc.2015.260
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum ribosome-binding protein 1, RRBP1, promotes progression of colorectal cancer and predicts an unfavourable prognosis

Abstract: Background:Ribosome-binding protein 1 (RRBP1) has been implicated in the regulation of unfolded protein response, which is involved in almost every aspect of cancer development. We aimed to explore the significance of RRBP1 in the progression and prognosis of colorectal cancer (CRC).Methods:The study population consisted of 856 patients with stage I–III CRC from two hospitals. RRBP1 expression was examined by immunohistochemisty (IHC) in colorectal tissues. The correlation of RRBP1 expression and CRC occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 41 publications
3
56
0
Order By: Relevance
“…These biologic roles likely account for the distinctive cytoplasmic and perinuclear ALK localization in EIMS with RRBP1-ALK fusions. RRBP1 overexpression has been implicated as a marker of poor prognosis in breast and colorectal cancer [19,20], but the IMT studies reported here are the first demonstration of an RRBP1 oncogenic mechanism. RRBP1-ALK retained the N-terminal RRBP1 coiled-coil domain (Figure 2 and Figure 3), and hence is one of various ALK fusion oncoproteins, such as TPM3-ALK [21], in which a coiled-coil fusion partner dictates ALK oncogenic activation.…”
Section: Discussionmentioning
confidence: 95%
“…These biologic roles likely account for the distinctive cytoplasmic and perinuclear ALK localization in EIMS with RRBP1-ALK fusions. RRBP1 overexpression has been implicated as a marker of poor prognosis in breast and colorectal cancer [19,20], but the IMT studies reported here are the first demonstration of an RRBP1 oncogenic mechanism. RRBP1-ALK retained the N-terminal RRBP1 coiled-coil domain (Figure 2 and Figure 3), and hence is one of various ALK fusion oncoproteins, such as TPM3-ALK [21], in which a coiled-coil fusion partner dictates ALK oncogenic activation.…”
Section: Discussionmentioning
confidence: 95%
“…This protein functions in post-translational processing of proteins secreted from the endoplasmic reticulum 41 and has been implicated in cell autophagy 42,43 . While these mutations have not been previously described for RRBP1, overexpression of this gene has been reported in other solid tumors, including breast and colorectal adenocarcinomas 44,45 . In non-metastatic colorectal cancer, high expression of RRBP1 has been described as a poor prognostic biomarker 44 .…”
Section: Discussionmentioning
confidence: 79%
“…While these mutations have not been previously described for RRBP1, overexpression of this gene has been reported in other solid tumors, including breast and colorectal adenocarcinomas 44,45 . In non-metastatic colorectal cancer, high expression of RRBP1 has been described as a poor prognostic biomarker 44 . While no effect on metastatic survival was noted in this population of patients with metastatic SCCA based on RRBP1 mutation status, our findings of this gene warrants further evaluation in future studies for anal cancer.…”
Section: Discussionmentioning
confidence: 79%
“…expression [41]. The up-regulation of FRMD4A was reported in human head and neck squamous cell carcinoma (HNSCC) and correlated with increased risks of relapse [42].…”
Section: Resultsmentioning
confidence: 99%